2017
DOI: 10.3390/v9080216
|View full text |Cite
|
Sign up to set email alerts
|

An Inactivated Novel Genotype Fowl Adenovirus 4 Protects Chickens against the Hydropericardium Syndrome That Recently Emerged in China

Abstract: Since 2015, China has experienced outbreaks of severe hydropericardium syndrome (HPS), associated with a novel genotype and hypervirulent fowl adenovirus serotype 4 (FAdV-4) infection, with a prevalence in various provinces of the country. This has resulted in huge economic losses in the poultry industry. The novel FAdV-4 showed new genome characters, such as the natural deletion of open reading frame (ORF) 19 and ORF 27 (1966 bp), and high pathogenicity toward chickens. These are coupled with severe hydroperi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 37 publications
(54 reference statements)
1
28
0
Order By: Relevance
“…This deletion includes two open reading frames, ORF19 and ORF29 (Fig. 2c), which were also present in the recent Chinese variants [16]. The 5 strains are similar to the recently reported highly virulent HLJ/15118 strain, and the non-pathogenic strains clustered into a subgroup.…”
Section: Resultssupporting
confidence: 71%
See 1 more Smart Citation
“…This deletion includes two open reading frames, ORF19 and ORF29 (Fig. 2c), which were also present in the recent Chinese variants [16]. The 5 strains are similar to the recently reported highly virulent HLJ/15118 strain, and the non-pathogenic strains clustered into a subgroup.…”
Section: Resultssupporting
confidence: 71%
“…Since 2015, a highly contagious disease with severe hydropericardium syndrome- inclusion body hepatitis (HPS-IBH) has spread in large-scale broiler farms in China [6, 17]. HPS-IBH disease results in a huge economic loss through caused a large number of chicken’s death [16]. In our study, five hypervirulent strains were isolated from several chicken farms in Eastern China and characterized to be serotype 4, based on phylogenetic analysis of the full length of genomic sequences.…”
Section: Discussionmentioning
confidence: 99%
“…No distinct clinical signs and pathological damage were observed in the immunized group, indicating that the developed vaccine was safe and could provide sufficient protection for chickens. In our study, the FAdV-4 specific antibody titers of the newly developed inactivated vaccine could reach at 6,300 in 14 days post single immunization, while the inactivated vaccine Pan et al [38] developed had an antibody titer of less than 4,000 in 14 days post single immunization, which indicated that the newly established inactivated vaccine could produce a higher level of antibodies. In addition, Kim et al [30] also developed an inactivated oil-emulsion fowl Adenovirus serotype 4 vaccine.…”
Section: Discussionmentioning
confidence: 49%
“…The remaining 15 clinical isolates were all from chickens with severe HHS from different provinces in China ( Table 1 ). Chicken liver hepatocellular carcinoma cell line (LMH cells) were cultured [ 30 ] in Dulbecco’s modified Eagle’s medium (DMEM) (Thermo Fisher Scientific, Waltham, MA, USA) supplemented with 15% fetal bovine serum (HyClone, South Logan, UT, USA), 100 IU/mL penicillin and 100 μg/mL streptomycin.…”
Section: Methodsmentioning
confidence: 99%